Australian medical students and their choice of surgery as a career: a review. Issue 9 (16th September 2013) - Grigg, Megan; Arora, Manit; Diwan, Ashish D.
Abstract Background Surgery is an emotionally, physically and mentally challenging profession, and medical students factor in many variables when choosing surgery as a career choice. The aim of this study is to review the available literature on the factors influencing Australian medical students' choice of surgery as their career. Method A search of EMBASE and MEDLINE with the search terms 'medical students' AND 'surgery'; 'medical students' AND 'career pathways'; 'medical students' AND 'career choices' was conducted. Additionally, Google Scholar and the reference list of some articles were canvassed for suitable areas of study. Results Lifestyle factors were the main reason influencing medical student's career choices. A balance between work, family and lifestyle was found to be important, and a surgical career choice was not always compatible with this. In particular, female students placed more importance on family and lifestyle factors when opting for non‐surgical careers. Positive exposure and/or experiences in a surgical environment, perceived prestige and perceived financial reward were associated with surgical career choice. Conclusions There is a need to better understand the factors influencing surgical and non‐surgical career choice among Australian medical students, and develop appropriate interventions to promote surgery as a career. This article does not discuss personality traits of people who go into surgery.